Clcf1/Crlf1a-mediated signaling is neuroprotective and required for Müller glia proliferation in the light-damaged zebrafish retina - Boyd, Patrick; Campbell, Leah J.; Hyde, David R. (Frontiers in Cell and Developmental Biology, 2023)
Zebrafish possess the innate ability to fully regenerate any neurons lost following a retinal injury. This response is mediated by Müller glia that reprogram and divide asymmetrically to produce neuronal precursor cells that differentiate into the lost neurons. However, little is understood about the early signals that induce this response. Ciliary neurotrophic factor (CNTF) was previously shown to be both neuroprotective and pro-proliferative within the zebrafish retina, however CNTF is not expressed following injury. Here we demonstrate that alternative ligands of the Ciliary neurotrophic factor receptor (CNTFR), such as Cardiotrophin-like cytokine factor 1 (Clcf1) and Cytokine receptor-like factor 1a (Crlf1a), are expressed within Müller glia of the light-damaged retina. We found that CNTFR, Clcf1, and Crlf1a are required for Müller glia proliferation in the light-damaged retina. Furthermore, intravitreal injection of CLCF1/CRLF1 protected against rod photoreceptor cell death in the light-damaged retina and induced proliferation of rod precursor cells in the undamaged retina, but not Müller glia. While rod precursor cell proliferation was previously shown to be Insulin-like growth factor 1 receptor (IGF-1R)-dependent, co-injection of IGF-1 with CLCF1/CRLF1 failed to induce further proliferation of either Müller glia or rod precursor cells. Together, these findings demonstrate that CNTFR ligands have a neuroprotective effect and are required for induction of Müller glia proliferation in the light-damaged zebrafish retina.